Semantic agent programming language : use and formalization - Cochez, Michael (2012)
This thesis gives an overview of languages used in the Semantic Web for data representation and querying. Then it gives a formalization of the Semantic Agent Programming Language (S-APL), which is a Semantic Web language for agent programming. The formalization consists of syntax and query definition, and definition of the dynamic structure of a S-APL document. Further, it is shown why the formalization is needed.